Preparation of activated carbon from a mixture (wood _ polymer) using microwave radiation - Khalid Owaid; Ahmed Thanoon; Mayada Ali (College of Education for Pure Sciences, 2013)
ABSTRACT The research work was aimed for  preparation of activated carbon from blending the wood of lead tree with variable ratio of polymers  organic glass(PMMA),recycled rubber (5,10,15)% after carbonization process for 3hrs at 350c° then an activation process by treating the product of carbonization process with(1:2)(carbonized materials :KOH)by heating with microwave oven for(4,8,12)min at 720 watt, many tests have been conducted on prepared activated carbon samples such as determining the activity of the samples through adsorption of iodine and methylene blue from aqueous  media, the density and humidity content were measured and all the properties were compared with commercial one from British and Russ.